Жоғары мектептің оқу-тəрбие процесіне педагогикалық инновацияны ендіру жолдары - Сабанбаев, Н.И.; Дандыбаева, А.С. (ҚарМУ баспасы, 2012)
В статье рассматриваются пути совершенствования педагогических инновационных технологий в ву- зе. Проанализированы научные исследования зарубежных и отечественных ученых по данному на- правлению, выделены виды, средства и методы педагогических инноваций, используемые в учебном процессе вуза, описаны их основные направления. Авторы отмечают, что инновационные технологии обучения формируют не только систему знаний, но и личностные и профессиональные характеристи- ки, необходимые будущему специалисту для саморазвития и успешной социализации в будущем. Ways of perfection of pedagogical innovative technologies in high school are considered in the article. Scientific researches of foreign and domestic scientists on problems of a pedagogical innovation in high school are also analyzed. Kinds, means and methods of pedagogical innovations used in educational process of high school are allocated. Basic directions about introduction of pedagogical innovations in high school are described by authors of the article. Innovative technologies of training form not only system of knowledge, but also the personal and professional characteristics necessary for the future expert for self-development and successful socialization in the future.
Keywords: жоғарғы мектеп; оқу-тәрбие процессі; педагогикалық инновацияны ендіру жолдары